MANAJEMEN PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMA NEGERI 7 SAROLANGUN - Perawati; Fridiyanto; Nugroho, Aris Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology requires the education sector to innovate learning processes that can enhance students’ learning motivation. Information technology based learning management has become one of the relevant strategies to address these challenges, particularly at the secondary school level. This study aims to analyze the planning, implementation, evaluation, as well as the supporting and inhibiting factors in the application of information technology based learning management to improve students’ learning motivation at tate Senior High School 7 Sarolangun. This study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with the principal, three teachers, and two students, classroom observations, and documentation of learning tools. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. The results indicate that learning planning has systematically integrated information technology into lesson plans and the selection of instructional media. The implementation of information technology–based learning is interactive and varied, which increases student engagement and learning motivation. Evaluation conducted through online quizzes, digital assignments, and technology-based projects was effective in improving students’ motivation to learn. The main supporting factors include school support, teacher readiness, and student enthusiasm, while the inhibiting factors include limited internet access and learning devices. Therefore, information technology based learning management can effectively enhance students’ learning motivation.